Bald eagle (Haliaeetus leucocephalus) population increases in Placentia Bay, Newfoundland: evidence for habitat saturation? - Karla R. Letto; Yolanda F. Wiersma; Joe Brazil; Bruce Rodrigues (Avian Conservation and Ecology, 2015)
Across North America, Bald Eagle (Haliaeetus leucocephalus) populations appear to be recovering following bans of DDT. A limited number of studies from across North America have recorded a surplus of nonbreeding adult Bald Eagles in dense populations when optimal habitat and food become limited. Placentia Bay, Newfoundland is one of these. The area has one of the highest densities of Bald Eagles in eastern North America, and has recently experienced an increase in the proportion of nonbreeding adults within the population. We tested whether the observed Bald Eagle population trends in Placentia Bay, Newfoundland during the breeding seasons 1990-2009 are due to habitat saturation. We found no significant differences in habitat or food resource characteristics between occupied territories and pseudo-absence data or between nest sites with high vs. low nest activity/occupancy rates. Therefore there is no evidence for habitat saturation for Bald Eagles in Placentia Bay and alternative hypotheses for the high proportion of nonbreeding adults should be considered. The Newfoundland population provides an interesting case for examination because it did not historically appear to be affected by pollution. An understanding of Bald Eagle population dynamics in a relatively pristine area with a high density can be informative for restoration and conservation of Bald Eagle populations elsewhere.